تقويم محتوى منهج التربية الإسلامية في المرحلة الثانوية على ضوء معايير المناهج من وجهة نظر المعلمين بالسودان - حسن، مبارك محمد; حمد، عمر إبراهيم رفاي (مركز بحوث ودراسات دول حوض البحر الأحمر وجامعة بخت الرضا, 2021)
هدفت الدراسة إلى تقويم محتوى منهج التربية الإسلامية في المرحلة الثانوية على ضوء معايير المناهج من وجهة نظر المعلمين بالسودان لمعرفة مدى تقويم محتوى منهج التربية الإسلامية في المرحلة الثانوية لتحقيق أهداف المنهج والتعرف على مدى استيفاء محتوى منهج التربية الإسلامية في المرحلة الثانوية لشروط ومعايير بناء المناهج. اتبعت الدراسة المنهج الوصفي والتحليلي، اختيرت عينة مكونة من 40 معلمة ومعلمة من معلمي التربية الإسلامية بالمدارس الثانوية بمحلية الجنينة ولاية غرب دارفور، تم اختيارهم بالطريقة القصدية، كما تم تحليل البيانات ببرنامج الحزم الإحصائية للعلوم الاجتماعية. توصلت الدراسة إلى عدة نتائج منها أن محتوى منهج التربية الإسلامية يراعي حاجات المتعلم، ويركز المحتوى على انبراز الجوانب التطبيقية للدروس، ويوجد توازن بن شمول المحتوى وعمقه. ختمت الدراسة بعدد من التوصيات منها ضرورة مراجعة مسألة الترابط والتكامل بن المواد المختلفة ومنهج التربية الإسلامية، ضرورة مواكبة منهج التربية الإسلامية بالمرحلة الثانوية التطور العلمي.
The study aimed to evaluate the content of the Islamic education curriculum in the secondary stage in light of the curriculum standards from the point of view of teachers in Sudan, to find out the extent to which the content of the Islamic education curriculum in the secondary stage is evaluated in order to achieve the objectives of the curriculum and to identify the extent to which the content of the Islamic education curriculum in the secondary stage meets the conditions and standards of curriculum construction. The study followed the descriptive and analytical approach. A sample of 40 female and male teachers from Islamic education teachers in secondary schools in El Geneina locality, West Darfur State, was chosen by the intentional method, and the data were analyzed in the Statistical Package for Social Sciences program. The study reached several conclusions, including that the content of the Islamic education curriculum takes into account the needs of the learner, and the content focuses on highlighting the practical aspects of the lessons, and there is a balance between the comprehensiveness and depth of the content. The study concluded with a number of recommendations, including the necessity to review the issue of interconnectedness and complementarity between the different subjects and the Islamic education curriculum, and the necessity to keep pace with the Islamic education curriculum at the secondary stage with scientific development
Keywords: التعليم الثانوي -- المناهج الدراسية -- تقويم المناهج -- معايير المناهج -- منهج التربية الإسلامية -- السودان